2008
DOI: 10.1002/zoo.20172
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient digestibility and fecal characteristics are different among captive exotic felids fed a beef‐based raw diet

Abstract: Nutrient digestibility has not been well characterized in exotic felids. The objective of this experiment was to evaluate differences in nutrient digestibility and fecal characteristics in five large exotic captive felid species, including bobcats, jaguars, cheetahs, Indochinese tigers, and Siberian tigers. All animals were individually housed and adapted to a beef-based raw diet (Nebraska Brand((R)) Special Beef Feline, North Platte, NE) for 16 d. Total fecal collections were conducted from days 17 to 20. Fec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
51
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 15 publications
10
51
1
Order By: Relevance
“…Data from Vester et al [2008] appear to indicate a higher capability of smaller felids for the digestion of TDF components (Fig. 7), in accord with the carnivore body size hypothesis; note that the measure of TDF also describes protein-polysaccharide complexes of connective tissues [reviewed in Sunvold et al, 1995a] that will be digested by gut microbes.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Data from Vester et al [2008] appear to indicate a higher capability of smaller felids for the digestion of TDF components (Fig. 7), in accord with the carnivore body size hypothesis; note that the measure of TDF also describes protein-polysaccharide complexes of connective tissues [reviewed in Sunvold et al, 1995a] that will be digested by gut microbes.…”
Section: Discussionmentioning
confidence: 50%
“…Microbial fermentation can and does take place in the large intestine (and the distal part of the small intestine) of canids and felids [Banta et al, 1979;Kienzle, 1994;Sunvold et al, 1995a,b;Buena et al, 2000;Hesta et al, 2001Hesta et al, , 2003Backus et al, 2002;Bosch et al, 2008;Janssens et al, 2008;Vester et al, 2008]. Data from Vester et al [2008] appear to indicate a higher capability of smaller felids for the digestion of TDF components (Fig.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The inability of felids to produce certain essential amino acids (e.g. taurine) renders bobcats as obligate carnivores [21,[29][30][31], and therefore bobcats consume little plant matter [3,23,25]. In contrast, gray foxes are facultative carnivores documented to seasonally supplement their diet with a high degree of plant matter, including persimmon (Diospyros virginiana), grapes (Vitis spp.…”
Section: Speciesmentioning
confidence: 99%
“…Lôbo Jr. et al (2001) reported that ADF underrated the CAD determined by total fecal collection, in contrast to Carciofi et al (1998), who deem CF and ADF efficient in this determination, but suggest the need for new studies to confirm such conclusion. Under these conditions, the reports of Vester et al (2008) and Clauss et al (2010), about the likelihood of microbial fermentation in the final portion of the small intestine and in the large intestine of small felines may justify the reduced CAD estimated by CF and ADF in the present experiment.…”
Section: Resultsmentioning
confidence: 60%